Kinetics of crystals growth under electron-beam crystallization of amorphous films of hafnium dioxide - Bagmut, A.G.; Bagmut, I.A. (Functional Materials, 2018)
Amorphous films of HfO₂ are prepared by laser ablation of Hf target in an oxygen atmosphere. Its crystallization was performed under the electron beam impact in a column of electron microscope. Formation and growth of HfO₂ crystals are investigated in situ. The transformation kinetic curves are plotted on the basis of a frame-by-frame analysis of the video recorded flick during the film crystallization. According to the structural and morphological features, the phase transformation corresponds to the dendrite polymorph crystallization and can be either single-stage or two-stage in nature. In the latter case, the size-phase effect takes place, consisting in the fact, that when the crystal of orthorhombic modification of HfO₂ reaches a critical size (~0.2 μm), it splits into domains with orthorhombic and monoclinic crystal lattices. The kinetic parameters of the crystallization are determined and it is shown, that the quadratic dependence of the fraction of the crystalline phase on time takes place. The average value of the relative length for the dendrite polymorphic crystallization is about 3075. The phase transition from the amorphous state to the crystalline one is accompanied by increasing of the relative density of matter of the film by about 2.5 %. The crystallized film consists predominantly of dendrites of the monoclinic modification of HfO₂.